Pleurochrysis carterae, a coccolithophorid alga: A potential sustainable feedstock for biological methane production - Ozer, Kubra; Taskan, Banu; Taskan, Ergin (Pergamon-Elsevier Science Ltd, 2026)
Coccolithophorid algae are known as the largest carbon sequesters and primary producers among the microalgae species. They also have the potential to produce significant amounts of lipids, which can be used as a renewable feedstock. This study aimed to investigate the biomethane production potential of Pleurochrysis carterae biomass for the first time. The experiments were conducted in laboratory-scale anaerobic batch reactors at various inoculum/substrate (I/S) ratios. Results showed that the I/S ratio had a significant impact on both biomethane production performance and microbial community. The cumulative biomethane yield ranged from 87.1 to 159.4 mL CH4/g-VS, depending on the I/S ratios, which ranged from 0.3 to 1.5. Microbial community analysis revealed the prevalence of Proteobacteria, Bacteroidetes, and Firmicutes phyla, known for their effectiveness in mesophilic anaerobic digestion (AD). Two kinetic models were utilized to verify the cumulative biomethane data, with the modified Gompertz model proving to be the best fit for the experimental results. The study also addressed the limitations and future prospects, emphasizing the need for further research to improve the scalability, costeffectiveness, and optimization of Pleurochrysis carterae for CH4 production.
Keywords: Pleurochrysis carterae; Coccolithophore; Feedstock; Anaerobic digestion; Biomethane production